A scoping review of the resources needed to deliver anterior cruciate ligament physiotherapy rehabilitation in randomised controlled trials. (3rd March 2020) - Dunphy, E.; Hamilton, F. L.; Button, K.; Murray, E.
Abstract: Background: The Anterior Cruciate Ligament (ACL) stabilises the knee and is commonly injured in sport. Surgical repair and rehabilitation are common. However, rehabilitation randomised controlled trials do not always report the resources used to deliver ACL rehabilitation. This may lead to suboptimal availability of resources for evidence based care. Objective: To identify the resources used to deliver multimodal ACL rehabilitation in randomised controlled trials Methods: Comprehensive searches, combining 'anterior cruciate ligament', and 'rehabilitation' with the Cochrane RCT filter, were conducted of Medline, Embase, Cinahl, PeDro, Sports Discus and the Cochrane Library. Adults post ACL reconstruction were included. The intervention and comparator were physiotherapy for post-operative rehabilitation. Outcomes were the resources required to deliver rehabilitation, and study type was randomised controlled trials. Papers were screened against the criteria; data were charted and narrative synthesis applied. Results: Fourteen studies reported on 599 patients. The interventions ranged from 4 to 36 weeks. Physiotherapy was typically an hour and ranged from 1 to 5 sessions/week. Resources included a gym environment with rehabilitation equipment such as resistance machines, free weights, cardiovascular and neuromuscular control equipment, and an experienced physiotherapist. Conclusions: Implications for future studies include the need for a more detailed report of the resources used in RCTs. Accurate reporting would help healthcare decision makers to effectively manage resources when implementing evidence based care. Findings can be considered as criteria against which to audit resource provision.